Efektivitas Hubungan Kerja Guru di SDN 4 Asparaga Kabupaten Gorontalo - Wawan Iskandar Gani; Novianty Djafri (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
The effectiveness of work relationships is a factor that plays an important role in organizational activities, it needs to be fostered and developed so that organizational goals can be achieved effectively. Organizational goals will be achieved if the organization has reliable, skilled and qualified human resources so that they can provide optimal contributions and improve work performance. Both for organizations, society and employees themselves. The effectiveness of work relations is a person's positive attitude or general condition towards organizational life. The approach in this research is to use an associative approach. The type of research used is descriptive qualitative. Data collection was carried out using observation and interview techniques. Based on the research results, there are several things that are used to measure a person's work effectiveness, namely (1) steady and smooth movements, (2) rhythmic movements, (3) responding more quickly to signs, (4) being able to predict difficulties that will arise, (5) ) works quietly. Thus, it can be concluded that (1) the effectiveness of employment relations is the level of a person's mastery of knowledge and skills in their work which can be measured from the length of service and the level of knowledge and skills they possess. Various efforts to fulfill teachers' needs to be good have been carried out quite well at SDN 4 Asparaga, Gorontalo Regency, (2) supporting factors for the effectiveness of teacher working relationships at SDN 4 Asparaga, Gorontalo Regency in the form of fulfilling several needs, namely physiological needs, security needs, social needs, Needs that reflect a sense of self, and teacher self-actualization needs.